Transvaginal Urethrolysis as a Treatment Option for Women with Recurrent Cystitis - Boonwong S. (2023)
Objective: To demonstrate the outcome of transvaginal urethrolysis as a treatment option for women with recurrent cystitis, which could be caused from voiding problems. In the case of a failure of non-invasive treatment, the surgical procedure to decrease outlet resistance may have a role. Materials and Methods: Between January 2016 and December 2020, women with recurrent cystitis who underwent urethrolysis at Siriraj Hospital were retrospectively reviewed. Only women who were followed-up for more than 6 months were analyzed. Cure was defined by no clinical symptoms of cystitis, no pyuria on urine analysis, and/or negative urine culture during the follow-up period. Results: In total, 52 women underwent transvaginal urethrolysis. The overall cure rate was observed 53.9% (28 cases) at a median follow-up time of 11.9 (6–59) months. Eighteen of the 44 cases (40.9%) who underwent a video urodynamics study showed bladder outlet obstruction, defined as a Solomon–Greenwell bladder outlet obstruction index of more than 5. None of the characteristics or urodynamics parameters showed statistically significant differences between the cure and failure groups. Postoperative urinary incontinence was reported in 14 cases (26.9%) but showed no statistical difference between the cure and failure group (p = 0.748). Conclusion: Bladder outlet obstruction is a common cause of recurrent cystitis. Transvaginal urethrolysis may have a role as treatment for women with recurrent cystitis from voiding dysfunction who have failed non and less-invasive treatments. Here, the overall cure rate was 53.8%. A factor associated with the cure rate could not be demonstrated in this study.